Social Entrepreneurship in Indonesian Bio-Electric Therapists with a Qualitative Approach - Tsabita Khwarazmita; Imam Mukhlis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Social entrepreneurship has the advantage of being based on a social vision and mission by solving social problems or challenges. It takes the form of social entrepreneurship carried out by social entrepreneurs. This research discusses exploring health as part of a social problem with a focus on social entrepreneurs in alternative health BE (Bio-Electric). Through in-depth interviews with five respondents as alternative health therapists in Indonesia who were selected in the East Java area. Data and information were collected through open questionnaires administered to respondents given to respondents who had the same questions as the interview. The data obtained relates to origin, education, type of entrepreneur, length of time, and type of entrepreneurship. When analyzing social therapist cases based on interview results, it was found that respondents 1) understood social entrepreneurship well, 2) they had consciously implemented this type of social entrepreneurship, 3) they explained a form of BE (Bio-Electric) therapy which did not require special skills, but still have to take training to find out more, 4) They have previous social experience relevant and not relevant to health, 5) They are very confident in their skills as therapists which apart from being able to help other people and help with social problems related to health, 6) Social experience underlies their social self-efficacy in carrying out social actions. This study investigates social entrepreneurship in alternative health therapists, with a focus on those working in the bioelectric domain. Based on their social experiences, the results show that these therapists are confident in their ability to contribute through social entrepreneurship. They possess advanced education and recognize the value of social interactions in their line of work. Because the profession is based on treatment experience and is estimated without a license, it is dubious. Involvement in religion is also proven to be essential to social entrepreneurship since it facilitates the process of social action. Although religion is sometimes disregarded in the study of entrepreneurship, its importance can strengthen the authority of studies in the area and present new challenges. According to the research, religion may boost the self-efficacy of alternative health therapists and motivate them to take social action.